2013
DOI: 10.3928/19425864-20131030-02
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Ice Hockey Skills Through Stroboscopic Visual Training: A Pilot Study

Abstract: Recent research has suggested that a new sport training tool may enhance vision, attention, and response timing. The tool, stroboscopic eyewear, includes lenses that alternate between transparent and opaque states to produce stroboscopic visual conditions. Previous research has demonstrated that stroboscopic training can improve visual abilities, but can stroboscopic training aff ect sport performance directly? The current pilot study explored this question by assessing athletic skill in professional ice hocke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 4 publications
2
77
2
1
Order By: Relevance
“…The amount of training undertaken by the EG participants in the current study far exceeds the 4 weeks deemed insufficient by Rezaee et al (2012) and is also considerably greater than other SVT studies which have produced significant findings (e.g. Appelbaum et al 2011;Appelbaum et al 2012;Holliday 2013;Mitroff et al 2013;Smith and Mitroff 2012;Wilkins and Gray 2015).…”
Section: Stroboscopic Trainingcontrasting
confidence: 51%
See 2 more Smart Citations
“…The amount of training undertaken by the EG participants in the current study far exceeds the 4 weeks deemed insufficient by Rezaee et al (2012) and is also considerably greater than other SVT studies which have produced significant findings (e.g. Appelbaum et al 2011;Appelbaum et al 2012;Holliday 2013;Mitroff et al 2013;Smith and Mitroff 2012;Wilkins and Gray 2015).…”
Section: Stroboscopic Trainingcontrasting
confidence: 51%
“…Skills such as central-field motion sensitivity (Appelbaum et al 2011), short-term visual memory (Appelbaum et al 2012), anticipation (Smith and Mitroff 2012), dynamic visual acuity (Holliday 2013), processing speed (Wilkins and Gray 2015), and accommodation ) have all been found to improve following a period of SVT. Whilst effects on motor performance are less researched, a pilot study by Mitroff et al (2013) showed a considerable increase in ice hockey shooting and passing performance for individuals who underwent SVT, whilst a control group saw no such improvements. Other studies have incorporated SVT as one of multiple tools in a visual training programme and found significantly increased baseball batting metrics (Clarke et al 2012) and significantly reduced concussion incidence (Clarke et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…68,69 Using a visual-disruption technology, such as stroboscopic glasses, provides an opportunity to supplement traditional interventions and may more closely mimic the cognitive stress of sport in the clinic. [59][60][61] …”
Section: Discussionmentioning
confidence: 99%
“…While there is growing evidence supporting benefits of many visual and perceptual training techniques, the current study sought to integrate approaches across the spectrum of these dimensions into a comprehensive Dynamic Vision Training program that includes many of the most promising individual training drills. Building on past research with tablet-based vision training [16], anticipatory timing training [57, 58], and stroboscopic visual training in simplified [25, 26, 29] and complex environments [27, 28], the current study assembled these techniques into a brief, adaptive training circuit. The goal of this DVT circuit was to offer diverse, challenging, and engaging training activities possessing a high correspondence in the MPFT framework with the sports-defined skillset of interest — baseball batting.…”
Section: Discussionmentioning
confidence: 99%